Synthesis, characterization and in vitro biological evaluation of the Schiff base derived from Benzidine and 1,3-Diphenyl-1,3-propanedione - Emir Horozić; Jasmin Suljagić; Darja Husejnagić; Nusreta Hasić; Amra Bratovčić (Journal of Engineering & Processing Management, 2019)
Schiff bases are organic compounds formed by the reaction of the primary amine with carbonyl compounds (aldehydes or ketones). These are mainly bi- or tridentate ligands capable of forming very stable complexes with transitional metals. They are used as catalysts in oxygenation, hydrolysis, electro-reduction and decomposition reactions. Many Shiff bases show significant anti-tumor and antimicrobial activity, which is why they are the subject of research by many scientists in the world. In this paper Schiff's base from benzidine and 1,3-diphenyl-1,3-propanedione was synthesized. To characterize the product, FTIR spectroscopy and stereo-microscopy were used. In order to determine biological activity, antibacterial, antifungal and antioxidant activity of the product was tested. The results showed that the interaction of benzidine and 1,3-diphenylpropandione results in a Schiff base showing antibacterial, antifungal and antioxidant activity.
Keywords: Schiff base; benzidine; FTIR; UV/Vis; antimicrobial activity